Identification of a novel human memory T-cell population with the characteristics of stem-like chemo-resistance. (2nd June 2016) - Murata, Kenji; Tsukahara, Tomohide; Emori, Makoto; Shibayama, Yuji; Mizushima, Emi; Matsumiya, Hiroshi; Yamashita, Keiji; Kaya, Mitsunori; Hirohashi, Yoshihiko; Kanaseki, Takayuki; Kubo, Terufumi; Himi, Tetsuo; et al.
ABSTRACT: High-dose chemotherapy may kill not only tumor cells but also immunocytes, and frequently induces severe lymphocytopenia. On the other hand, patients who recover from the nadir maintain immunity against infection, suggesting the existence of an unknown memory T-cell population with stress resistance, long-living capacity, proliferation and differentiation. Recently, the differentiation system of T-cell memory has been clarified using mouse models. However, the human T-cell memory system has great diversity induced by natural antigens derived from many pathogens and tumor cells throughout life, and profoundly differs from the mouse memory system constructed using artificial antigens and transgenic T cells. Here we report a novel human T-cell memory population, "young memory" T (TYM ) cells. TYM cells are defined by positive expression of CD73, which represents high aldehyde dehydrogenase 1 (ALDH1) activity and CXCR3 among CD8 + CD45RA + CD62L + T cells. TYM proliferate upon TCR stimulation, with differentiation capacity into TCM and TEM and drug resistance. Moreover, TYM are involved in memory function for viral and tumor-associated antigens in healthy donors and cancer patients, respectively. Regulation of TYM might be very attractive for peptide vaccination, adoptive cell-transfer therapy and hematopoietic stem cell transplantation.